Impactos da pandemia por COVID-19 no contexto de trabalho de profissionais de saúde na atenção básica de saúde - Rienzo, Israel Roberto de (Universidade Federal de São Carlos, 2022)
In pandemic contexts, the work in health becomes even more challenging, which reflects the need for further studies to understand the relationship between its elements. This research is configured as empirical, interpretative, under a quantitative-qualitative approach, and its objective was to investigate and understand the impacts of the pandemic in the work context of health professionals in Primary Health Care (PHC) in a medium-sized municipality in the interior of São Paulo. Thus, the initial invited population was made up of Basic Health Units (BHU) and Family Health Unit (FHU) teams from that municipality, totaling approximately 340 people in the first stage of the fieldwork. The data production was built from the theoretical referential of Sociology and Psychodynamics of Work and was composed of two stages: i) application of the Inventory of Pathogenic Suffering Risks at Work (IRIS); ii) a questionnaire prepared by the researchers aiming at exploring the impacts of the pandemic on the health and praxis of the professionals, which will be applied only to the participants who present risks of pathogenic suffering at work according to IRIS. The data analysis for IRIS followed the instrument's validation normative, and the questionnaire from the Thematic Content Analysis. The results produced were divided into three thematic categories, each with its respective cores and sub-cores of analysis. The first category is Work overload for health professionals in the context of the Covid-19 pandemic, which sought to portray both the working conditions, understood from the various factors of daily work that contributed to the excess demand and the pressures that health professionals experience daily in this context (work overload) and how the health work during the pandemic was structured and the consequences of this structuring on the mental health of health professionals (work processes). The category Psychic suffering of health professionals in the work context in the Covid-19 pandemic sought to portray the ways in which health professionals of the ABS of São Carlos experienced psychic suffering in the work context during the Covid-19 pandemic, either through the expressions of suffering at work (Creative Suffering and Pathogenic Suffering), by the interlocations between real work and prescribed work or by the (absence) of valuation at work. Finally, the category Processes of stigmatization of health professionals during the Covid-19 pandemic sought to portray the logic of devaluation of health professionals, which can be seen indirectly both by questioning their work (whether there was vaccine in the syringe) and by a government that not only invested in "drugs" for Covid-19 without scientific evidence, wasting public money, but also used and uses these professionals as scapegoats as a defense strategy against its decisions, feeding the stigma on the public servant. It was concluded that it is fundamental to understand the neoliberal logic of devaluation of the health professional and the precariousness of work relations, so that strategies of health promotion - directed to the health professionals themselves - as well as strategies of valorization and valorization of the SUS can be proposed. Thus, this study can contribute to the proposition of better guidelines for Permanent Health Education (PHE) and support actions for the Mental Health of the worker.
Impacts of the COVID-19 pandemic on the work context of health professionals in Primary Health Care
Keywords: Covid 19; Atenção Básica à Saúde; Equipe de Saúde; Saúde do trabalhador; Saúde Mental; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL